Puzzling asteroid 21 Lutetia: our knowledge prior to the Rosetta fly-by - Belskaya, I. N. (2010)
Aims. A wide observational campaign was carried out in 2004–2009 that aimed to complete the ground-based investigation of Lutetia prior to the Rosetta fly-by in July 2010. Methods. We obtained BVRI photometric and V-band polarimetric measurements over a wide range of phase angles, and visible and infrared spectra in the 0.4–2.4 μm range. We analyze them with previously published data to retrieve information about Lutetia's surface properties. Results. Values of lightcurve amplitudes, absolute magnitude, opposition effect, phase coefficient, and BVRI colors of Lutetia surface seen at near pole-on aspect are determined. We define more precisely parameters of polarization phase curve and show their distinct deviation from any other moderate-albedo asteroid. An indication of possible variations in both polarization and spectral data across the asteroid surface are found. To explain features found by different techniques, we propose that (i) Lutetia has a non-convex shape, probably due to a large crater, and heterogeneous surface properties probably related to surface morphology; (ii) at least part of the surface is covered by a fine-grained regolith of particle size smaller than 20 μm; (iii) the closest meteorite analogues of Lutetia's surface composition are particular types of carbonaceous chondrites, or Lutetia has specific surface composition that is not representative among studied meteorites.